(untitled) (Brazilian Journal of Behavioral and Cognitive Therapy, 2005)
Atopic dermatitis, psoriasis, and vitiligo are chronic skin diseases in which prognosis, evolution, the kinds of required cares, and the visibility of the condition constitute factors that affect both the patient’s and their parents´ behavior. The main difficulty faced up by the person who has one of such diseases is the fact that he/she becomes a constant target of discrimination and prejudice. This study aims to demonstrate some stigmatization effects in the narrative of children with chronic dermatoses. To this purpose, six chronic skin disease affected children, between seven and eight years old, created, individually, a text for the characters of a children’s tale. The results showed that prejudice and stigmatization are present in different social contexts and there are difficulties for children as well as their family to faceupto these situations in a proper way.